2013
DOI: 10.1093/gji/ggs132
|View full text |Cite
|
Sign up to set email alerts
|

A parametric analysis of two-dimensional elastic full waveform inversion of teleseismic data for lithospheric imaging

Abstract: The development of dense networks of broad-band seismographs makes teleseismic data amenable to full-waveform inversion (FWI) methods for high-resolution lithospheric imaging. Compared to scattered-field migration, FWI seeks to involve the full seismic wavefield in the inversion. We present a parametric analysis of 2-D frequency-domain FWI in the framework of lithospheric imaging from teleseismic data to identify the main factors that impact on the quality of the reconstructed compressional (P)-wave and shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…The main difficulty is to separate the contribution of P-to-S conversions from those of crustal multiples that will produce deep artefacts in the migrated section. While it has been demonstrated that including multiples in the imaging process improves the angular distribution of scattering, in particular in the backward direction, thus providing better images of the subsurface (Bostock et al 2001;Pageot et al 2013), because of their extra reflection beneath the free surface, those multiples are more sensitive to topography (Monteiller et al 2013) and to crustal heterogeneity than primary conversions. As a result, if receiver functions have a sufficiently broad azimuthal and incidence angle distribution, a simple stack is usually sufficient to separate the coherent contribution of primary conversions.…”
Section: I G R At I O N O F T E L E S E I S M I C P -T O -S C O N Vmentioning
confidence: 99%
“…The main difficulty is to separate the contribution of P-to-S conversions from those of crustal multiples that will produce deep artefacts in the migrated section. While it has been demonstrated that including multiples in the imaging process improves the angular distribution of scattering, in particular in the backward direction, thus providing better images of the subsurface (Bostock et al 2001;Pageot et al 2013), because of their extra reflection beneath the free surface, those multiples are more sensitive to topography (Monteiller et al 2013) and to crustal heterogeneity than primary conversions. As a result, if receiver functions have a sufficiently broad azimuthal and incidence angle distribution, a simple stack is usually sufficient to separate the coherent contribution of primary conversions.…”
Section: I G R At I O N O F T E L E S E I S M I C P -T O -S C O N Vmentioning
confidence: 99%
“…unprecedented resolution based on converted or scattered teleseismic waves [e.g., Rondenay, 2009;Shang et al, 2012;Pageot et al, 2013], especially in the framework of adjoint tomography [Tong et al, 2014].…”
Section: 1002/2014gl061644mentioning
confidence: 99%
“…Teleseismic array imaging based on converted and scattered waves is one of the essential tools for investigating the crustal and upper mantle structures, and has contributed significantly over the past three decades to our understanding of tectonic evolution and internal geodynamic processes [e.g., Rondenay, 2009;Kind et al, 2012;Liu and Gu, 2012]. Various methods including receiver function (RF) analysis through single station stacking [e.g., Langston, 1977;Yan and Clayton, 2007], common conversion point (CCP) stacking [e.g., Revenaugh, 1995;Sheehan et al, 2000;Chen et al, 2005], inverse scattering approaches based on asymptotic methods such as generalized Radon transform [e.g., Bostock et al, 2001;Cao et al, 2010;Shang et al, 2014], teleseismic migration [e.g., Shragge et al, 2006;Shang et al, 2012], and teleseismic scattering tomography [e.g., Frederiksen and Revenaugh, 2004;Pageot et al, 2013;Burdick et al, 2014;Tong et al, 2014] have been developed for specific imaging purposes. RF analysis is a routine tool to characterize major discontinuities of the Earth's subsurface such as the Moho, 410 km and 660 km discontinuities [e.g., Rondenay, 2009;Kind et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative is to model the full scat-tered wavefield, to account for internal multiples with the scattered-field formulation (i.e., Pageot et al, 2013). An alternative is to model the full scat-tered wavefield, to account for internal multiples with the scattered-field formulation (i.e., Pageot et al, 2013).…”
mentioning
confidence: 99%
“…In this Appendix, for the sake of simplicity, we choose to model the reflection wavefield with the single-scattering Born approximation. An alternative is to model the full scat-tered wavefield, to account for internal multiples with the scattered-field formulation (i.e., Pageot et al, 2013). This simply amounts to replacing A(m 0 ) by A(m 0 + δm) in the lefthand-side of equation (A2).…”
mentioning
confidence: 99%